THE INFLUENCE OF PROBLEM-BASED LEARNING MODEL IN IMPROVING STUDENT ENGAGEMENT IN MATHEMATICS - Lovika Ardana Riswari; Henry Suryo Bintoro (Department of Primary education, Faculty of Teacher Training and Education, Universitas Su, 2020)
AbstractThe purpose of this research is to determine the effect of the problem-based learning model in improving student engagement on mathematics subjects. This type of research is an quasi-experimental with the pretest-posttest control group design approach. The independent variables of this research are Problem-Based Learning and student engagement models in mathematics as the dependent variable. Participants in this research were 60 elementary school students who were divided into 2 groups, first were 30 elementary school students K1 as the experimental group who received learning with problem-based learning model and 30 elementary school students K2 as the control group that received the conventional learning model. Data collection techniques in this research using non-test techniques consisting of observation, questionnaires, and documentation. The data were analyzed by independent samples test. The results showed there was a significant influence of learning using problem-based learning model could improve student engagement in mathematics.Keywords: Problem Based Learning; Student Engagement.